Growing demand for housing and the productivity challenges in developing housing projects in Iraq - Ali Hassoon; Farid Ezanee Mohamed Ghazali; Tareq Khaleel; Ahmed Hadi (Journal of Infrastructure Preservation and Resilience)
Abstract The housing sector in Iraq is facing growing demand. However, productivity challenges continue to hinder the timely and efficient delivery of residential projects. Recognising the urgent need to increase construction productivity (CP) in this sector, this study investigates critical factors that impact the performance of horizontal housing projects in Iraq. The novelty of this research lies in its focus on housing skeleton tasks, such as foundations, brickwork, and slabs, which are pivotal to project efficiency. A structured questionnaire was developed, encompassing 47 factors distributed across the planning, design, and construction phases. The survey was administered to a range of industry stakeholders, including project managers, consultants, engineers, and supervisors, and it achieved a high response rate of 79.6%. The results were analysed via a modified weighted relative importance index (RII), which incorporates respondents’ experience levels to yield a nuanced understanding of each factor’s impact. The key findings reveal that planning (RII = 0.874), team size (RII = 0.856), quantity of brickwork (RII = 0.838), supervision (RII = 0.815), and unit area (RII = 0.793) are among the most influential factors on CP. These insights provide valuable guidance for researchers and practitioners in identifying areas for strategic improvement, ultimately supporting the capacity of Iraq’s housing sector to meet escalating demands.